Reducción de los tiempos de cambio de molde en la línea de inyección de preformas de la Compañía PLÁSTICOS TEAM S.A.S. - Castillo Morán, Rodrigo Alberto (Ingenierias, 2017)
In this research work are developed improvement tools that seeks to reduce mold change times in the Preforms Injection Line of the company Plasticos TEAM S.A.S., through the DMAIC methodology. Through the Company's Loss Tree, it is determined that scheduled routine stops are the second cause of downtime in the preform line and that working on optimizing mold changes will improve the availability of machines to increase production volume. Through the DMAIC methodology the specific objectives are developed that are implemented by means of three phases that starts with the current identification of the process, then by means of the data of the different changes of mold are obtained registers where they are grafican to measure the Variations in the process and the use of tools that provide possible solutions contributing to the reduction of mold change times, such as: Diagram Cause - Effect, Analysis of Causes, Analysis Impact - Effort. In the third phase of the development of the Objectives, the SMED tool is implemented for the reduction of mold change times of the three types of change that the Preform Injection line has: Complete, Semi-complete and Hearts. The overall objective of the work is to reduce the mold change time by 20%. The success of the development of this work is the commitment of the High Management and the training and training to the personnel so that everyone knows the technique and contribute ideas in this sense, and the team work to achieve a harmony and alignment of objectives of all the Areas to achieve reduction of mold change times.